2011
DOI: 10.1080/19406940.2011.627359
|View full text |Cite
|
Sign up to set email alerts
|

Social capital development among ethnic minorities in mixed and separate sport clubs

Abstract: Universiteit Brussel, Brussels, BelgiumDuring the past few decades, policymakers have had increasing expectations of sport in relation to the social integration of ethnic minorities. From a policy perspective, mixed organized sport is often advocated in order to bring people of diverse cultures in contact with each other which, in turn, is believed to foster interethnic tolerance and solidarity. At the same time, there is the perception that separate organized sport impedes the integration of ethnic minorities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 30 publications
4
30
0
8
Order By: Relevance
“…An important part of the results of these investigations has indicated that sport is a favorable element for the contexts related to the phenomenon of immigration. In concrete terms, these studies show that sport cooperates positively with: (a) the acquisition of social and cultural capital [20][21][22][23]; (b) maintaining cultural identity and cohesion around it [64]; (c) the interaction between "culturally different" [18,[24][25][26]; and (d) the creation of intercultural networks [27].…”
Section: Can Sport Help In the Social Inclusion Of The Immigrant Popumentioning
confidence: 99%
See 1 more Smart Citation
“…An important part of the results of these investigations has indicated that sport is a favorable element for the contexts related to the phenomenon of immigration. In concrete terms, these studies show that sport cooperates positively with: (a) the acquisition of social and cultural capital [20][21][22][23]; (b) maintaining cultural identity and cohesion around it [64]; (c) the interaction between "culturally different" [18,[24][25][26]; and (d) the creation of intercultural networks [27].…”
Section: Can Sport Help In the Social Inclusion Of The Immigrant Popumentioning
confidence: 99%
“…The specific literature on this matter indicates that sport offers important possibilities for the contexts that present immigrant population, because it favors: (a) the acquisition of social and cultural capital [20][21][22][23]; (b) the maintaining of cultural identity and cohesion around it [10]; (c) the interaction between "culturally different" [18,[24][25][26]; and (d) the creation of intercultural…”
Section: Introductionmentioning
confidence: 99%
“…Existe coincidencia respecto a que los métodos empleados o contextos de trabajo son determinantes; el deporte aumenta su potencial intercultural en entornos que promueven valores sociales y respeto mutuo (Hatzigeorgiadis et al, 2013;Li, Sotiriadou, & Auld, 2015), permitiendo la adquisición de capital social extrapolable fuera del deporte (Theebom, Schaillée, & Nols, 2012) y la adaptación a contextos con diversidad cultural (Allen et al, 2010); facilitando así la inclusión de colectivos inmigrantes (Tirone, Livingston, Miler, & Smith, 2010). Los programas deportivos comunitarios han demostrado ser efectivos para estos fines (Forde, Lee, Mills, & Frisby, 2015) siempre que se eviten segregaciones o las "automarginaciones" que puedan producirse (Makarova & Herzog, 2014).…”
Section: Inmigración Deporte E Integraciónunclassified
“…Además, situaciones como la anteriormente descrita podría producir diferencias en la adqusición de capital social entre hombres y mujeres (Pfister, 2004;Theebom et al, 2012). Sin embargo, éste tipo de situaciones ocurrió sólo en algunos grupos específicos (con momitores de menos experiencia) y de forma aislada con algunas niñas, sin que se configure como una conducta o actitud constante.…”
Section: Carter-thuillier Et Al -Integración De Los Estudiantes Inmiunclassified
“…Separated sport activities can also provide members of disempowered groups with temporary relief from the strain habitually experienced in their everyday asymmetrical interactions (Krouwel et al 2006). Moreover, the simplistic idea that segregated sports activities only reinforce bonding social capital, whereas mixed activity generates bridging social capital, has been questioned by several studies (Elling, De Knop, and Knoppers 2001;Janssens and Verweel 2014;Spaaij 2012;Theeboom, Schaillée, and Nols 2012).…”
Section: Women (Forced) Migrants and Sport-for-developmentmentioning
confidence: 99%